INTERACTIVE LEARNING MODUL (ILM) BERBASIS MASALAH BERIMPLEMENTASI PADA PROJECT MENGGUNAKAN FLIPBOOK - Wati, Rani Fajar; Rosa, Friska Octavia; Prameswari, Estika; Oktarina, Oktarina; Qolbi, Intan Sovi Aghnia; Mawarni, Sri Arum (Jurnal Pendidikan Fisika FKIP UM Metro, 2024)
Current learning requires students to be more interactive and utilize technology in the learning process. Achieving learning goals using technology can be developed by combining learning models and methods, one of which is problem-based learning implemented in projects. The aim of this research is to develop a problem-based Physics Interactive Learning Module (ILM) implemented in a project using a flipbook for students' creative thinking abilities. This research uses the development method with the ADDIE model. The instrument used to measure the level of validity of the instrument uses validation sheets from material and media experts. Meanwhile, the instrument used to measure creative thinking abilities uses an observation sheet. The validation results obtained by material experts and material experts were an average of 83.51% with very valid criteria. The product is then tested to see its effectiveness on creative thinking abilities. The results of the paired sample t test show a significance value of less than 0.05, so it is concluded that there is an influence of the use of ILM on creative thinking.